Bentuk Campur Kode Dalam Lirik Lagu Che’nelle - Viona Viona; Imelda Imelda; Harisal Harisal (Mezurashii: Journal of Japanese Studies, 2025)
Code-mixing is a general term that refers to the alternating use of two or more languages or language variations for communication purposes. The purpose of this study is to describe the form of code-mixing that appears in Che'nelle's song lyrics. The method that will be used in this study is a qualitative descriptive method, which is a method whose data is described through or with words. This method is considered a method that is in line with identifying code mixing in Che'nelle's song lyrics. The data contained in the study is a form of dialogue from each character which will later be interpreted into sentences or written words. The primary data source for this study was obtained through YouTube Music through the lyrics in Che'nelle's songs and Japanese translation texts; In contrast, secondary data sources include books, literature, and internet sites that are relevant to the research topic being conducted. Data analysis was carried out using the listening method and note-taking technique. The results showed that the code-mixing that appears in Cha'nelle's song lyrics consists of various forms such as words, phrases, clauses, and word repetitions. This code-mixing phenomenon often occurs when Japanese is mixed with English, either in one verse of a song or between verses. Keywords : code-mixing; sociolinguistics; song lyrics; cha’nelle